Fatores epidemiológicos associados a doenças respiratórias em potros Puro Sangue Inglês em quatro propriedades na região de Bagé/RS, Brasil - Ribas, Leandro do Monte (2008)
The present study has the objective to evaluate the epidemiologic factors related to respiratory diseases in thoroughbred foals placed in four stud farms around the city of Bagé/RS region, Brazil. Apart from the collection of data linked to breeding management practices, the evaluations consisted of the diary clinical control and complementary examinations for diagnosis using secretions collected from the respiratory tract of the foals affected with respiratory diseases. Among the 349 monitored foals until their 180 days of life, the incidence of 9,5% (33) of respiratory cases with 0,57% (2) of mortality was recorded. The concentration of cases was higher in months of summer, the 120 and 180 days old foals were more susceptible. The occurrence of the diseases was influenced by the breeding system and management practices that increased the environmental contamination potential, and also by the contact among the foals. No clinic case was related to the equine influenza virus (EIV) and to the equine herpesvirus (EHV) pathogens. Among the isolated pathogens, the highest frequency was for Streptococcus equi (57%), followed by Rhodococcus equi (17%) and this one was responsible for 50% of lethality. The obtained results suggest that connected factors to the management in the breeding of thoroughbred equine are going to contribute decisively for the manifestation of the respiratory disease and alert for the high morbidity caused by the equine adenitis and the high lethality related to Rhodococcus equi pathogens.